Patient experiences of alcohol specialist nurse interventions in a general hospital, and onwards care pathways. (16th February 2021) - Dorey, Lucy; Lathlean, Judith; Roderick, Paul; Westwood, Greta
Abstract: Aims: To provide insight into patient experiences of a general hospital‐based alcohol specialist nurse intervention during alcohol detoxification, experiences of alcohol specialist nurse hospital‐based follow‐up appointments (Pathway A) as well as the experiences of patients who did not have access to this additional help post detoxification (Pathway B). Design: A longitudinal qualitative study. Methods: A thematic analysis of semi‐structured interviews (2016–2017) with 24 patient participants ( N = 12 in each pathway; purposive selection) 1–4 weeks post‐detoxification and at 3 and 6 months, to identify patient experiences of these interventions. Results: Participants gave accounts of how 'empathic' and 'straight talking' interactions with alcohol specialist nurses during detoxification helped them to 'open up' and orient towards change. After detoxification follow‐up, outpatient appointments in the hospital setting were seen as supporting change in early recovery and engagement with a wider range of services. Those with no access to nurse follow‐up described experiencing a 'void' in available help. Participants in both groups described barriers to engagement with community alcohol services, peer groups and access to help for mild‐moderate mental health problems. Conclusion: Patient accounts indicate alcohol specialist nurse interventions during and after unplanned detoxification in a hospital setting can help orient patients towards change and support early recovery. Impact: Providing alcohol specialist nurse interventions in general hospitals offers one route to initiating recovery in alcohol‐dependent patients. This has potential to improve the lives of those affected and to reduce related demands on hospital services, but further research is needed. 摘要: 目的: 深入了解酒精戒毒期间, 综合医院酒精专科护士对患者采取的干预措施, 综合医院酒精专科护士随访坐诊的经历 (途径A) 以及未获得此类额外援助的患者的戒毒后经历 (途径B) 。 设计: 一项纵向定性研究。 方法: 开展主题分析, 对戒毒后1‐4周、3个月和6个月的24名病患参与者进行半结构化访谈 (2016年‐2017年), 以确定患者对此类干预措施的体验。 结果: 参与者讲述戒毒期间其与酒精专科护士的"同理经历"和"直接"互动, 以及此类互动如何帮助其"敞开心扉"并适应相关变化。如果在戒毒随访后预约医院门诊, 即可视为支持早期康复变更和参与更广泛的服务。无法获得护士随访的患者表示, 尽管已获得帮助, 其内心仍感觉"空虚"。两组参与者都对参与社区酒精服务、同龄人群体和获得轻度‐中度精神健康问题援助时遇到的障碍进行描述。 结论: 据患者描述, 如已在医院进行计划外解毒, 则在此期间和之后, 酒精专科护士可采取干预措施, 以帮助患者适应改变并对其早期康复予以支持。 影响: 酒精专科护士在综合医院内部采取干预措施, 从而帮助酒精依赖患者康复。此做法可能改善受影响者的生活, 减少对医院服务的相关需求, 然而, 仍应进一步展开研究。